Guide for authors: jCEC Template - Ivan Carlos Franco; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Authors must use the Microsoft Word template to prepare their manuscript. Using the template file will substantially shorten the time to complete copy-editing and publication of accepted manuscripts. If this is a problem, please contact the Editorial Office jcec.journal@ufv.br.